Comparative analysis of the behavior of reinforced concrete buildings using static equivalent, response spectrum, and time history methods - Made Hendra Prayoga; Ida Bagus Prastha Bhisama; P. Adi Yasa (Privietlab, 2026)
In structural analysis, earthquake loads are generally calculated using either equivalent static or dynamic approaches (response spectrum and time history), as specified in the SNI 1726:2019. This study aims to evaluate and compare the behavior of the Collins Boulevard Apartment building structure under earthquake loads using these three methods. The analysis was conducted using the structural modeling of a high-rise building with a dual system. For the time history method, three real earthquake records were used: Chi-Chi, Ibaraki Off, and Tohoku, which represent shallow crustal, Benioff, and megathrust earthquake sources, respectively. The results indicate that the equivalent static method produced the highest base shear of 51,761 kN, followed by the response spectrum method with ratios of 0.55 and 0.51 for the X and Y directions, respectively, relative to the static value, and the time history method with ratios of 0.48 and 0.42 for the X and Y directions, respectively. The maximum inter-story drift occurred in the equivalent static method, exceeding the allowable limit specified in SNI 1726:2019, while the two dynamic methods remained within safe limits. The internal forces in the beams and columns ranged from 0.3–0.9 times those produced by the static method, with the time history method exhibiting more fluctuating yet realistic structural responses.